Crescimento de três clones de umezeiro (Prunus mume Sieb. et Zucc.) e pessegueiro cv. Okinawa (Prunus persica (L.) Batsch.) propagados por estacas herbáceas - Mayer, Newton Alex [UNESP]; Pereira, Fernando Mendes [UNESP] (Sociedade Brasileira de Fruticultura, 2004)
Mume (Prunus mume Sieb. et Zucc.) presents promising characteristics for use as rootstock for peach and nectarines trees, however, when adopted the sexual propagation, it results in very heterogeneous plants, as a function of the mume's great genetic variability. Three clones (Clones 05, 10 and 15), selected from plants grown in the Estação Experimental de Jundiaí (IAC), São Paulo State, Brazil, propagated vegetatively and maintained in FCAV/UNESP, Jaboticabal Campus, have been object of several studies to make possible the agronomical use of these materials. The present study had for objective to evaluate the growth of three mume clones and 'Okinawa' peach propagated by herbaceous cuttings. The rooted cuttings were transplanted for plastic bags, maintained in nursery conditions and evaluated (stem diameter and length) up to 145 days. The mume Clones 05, 10 and 15 presented continuous growth with relationship to stem length, while 'Okinawa' peach stabilized growth 100 days after transplant, reflecting in lower plants. Differences don't exist among the mume clones studied in stem diameter after 100 days and stem length after 115 days of rooted cuttings transplant. 'Okinawa' peach presents larger stem diameter in relation to mume Clones 05, 10 and 15, what defines larger percentage of capable rootstocks for accomplishment of graft.

O umezeiro (Prunus mume Sieb. et Zucc.) apresenta promissoras características para utilização como porta-enxerto para pessegueiro e nectarineira; entretanto, quando adotada a propagação sexuada, as plantas apresentam-se muito heterogêneas, em função da grande variabilidade genética da espécie. Três clones (Clones 05; 10 e 15), selecionados a partir de plantas em cultivo na Estação Experimental de Jundiaí-SP (IAC), propagados assexuadamente e mantidos na FCAV/UNESP, Câmpus de Jaboticabal-SP, têm sido objeto de diversos estudos para viabilizar agronomicamente estes materiais. O presente estudo teve por objetivo avaliar o crescimento de três clones de umezeiro e do pessegueiro cv. Okinawa propagados por estacas herbáceas. As estacas enraizadas foram transplantadas para sacolas plásticas, mantidas em condição de viveiro telado, e avaliadas (diâmetro e comprimento da haste) até 145 dias. Os Clones 05; 10 e 15 de umezeiro apresentam crescimento contínuo com relação ao comprimento da haste, enquanto a cv. Okinawa estabiliza o crescimento após 100 dias do transplantio, refletindo-se em plantas mais baixas. Não existem diferenças entre os clones de umezeiro estudados no diâmetro da haste após 100 dias e no comprimento da haste após 115 dias do transplantio das estacas enraizadas. A cv. Okinawa apresenta maior diâmetro da haste em relação aos Clones 05; 10 e 15 de umezeiro, o que define maior porcentagem de porta-enxertos aptos à realização da enxertia.
Growth of three mume clones (Prunus mume Sieb. et Zucc.) and 'Okinawa' peach (Prunus persica (L.) Batsch.) propagated by herbaceous cuttings
Keywords: Rootstock; vegetative propagation; Prunus spp; Porta-enxerto; propagação vegetativa; Prunus spp